Lipid droplet biogenesis in the ovary - Megumi Ibayashi; Satoshi Tsukamoto (Reproductive Medicine and Biology, 2024)
Abstract Background Lipid droplets (LDs) are organelles consisting of a central core of neutral lipids covered by a single layer of phospholipids and are found in most eukaryotic cells. Accumulating evidence suggests that LDs not only store neutral lipids but also coordinate with other organelles for lipid metabolism within cells. Methods This review focuses on the synthesis of LDs during follicular development and highlights the factors involved in the regulation of LD biogenesis within the ovary. Main Findings In the mammalian ovary, the presence of LDs has long been recognized mainly by morphological analysis. However, their distribution in the ovary varies according to the region and cell type; for example, LDs are abundant in the medulla, which has a rich blood vessel network, in interstitial cells, which are the site of steroid production, and surrounding growing follicles, while they are poor in granulosa cells within follicles. LDs are also enriched in the corpus luteum after ovulation and massively accumulate in atretic follicles during follicular growth. Furthermore, LD synthesis is synchronized with angiogenesis during follicular development. Conclusion Addressing the functional link between LD biogenesis and angiogenesis is essential for understanding the molecular basis underlying LD biology, as well as the ovarian dysfunction with metabolic disorders.